Immediate impact of COVID-19 across tropical small-scale fishing communities. (1st February 2021) - Campbell, Stuart J.; Jakub, Raymond; Valdivia, Abel; Setiawan, Haris; Setiawan, Agus; Cox, Courtney; Kiyo, Askabul; Darman,; Djafar, Lely Fajriah; Rosa, Emilio de la; Suherfian, Wahid; Yuliani, Ade; et al.
Abstract: The volume and value of fish catches by Indonesia's small-scale fisheries have declined significantly since national government restrictions on travel and social distancing were imposed in response to the COVID-19 pandemic. Using a digital data collection system (OurFish), that records purchases by fish traders from small-scale fishers, data was collected across 82 coastal communities in Southeast Sulawesi. We found that the number of active fishers and traders declined by more than 90% after the onset of the pandemic and the average weight of catch per fishing trip increased across fishers. Although the average price per kilogram of fish declined after the pandemic began, fishers that were able to maintain fishing had on average higher catches and therefore daily catch value was maintained. High value fisheries that usually enter export supply chains were more negatively impacted compared with lower value species that are commonly sold to local markets. We interviewed 185 small scale fishers and fish traders across 20 of the 82 communities in Southeast Sulawesi province, recording the perceived level of impact on local fisheries and the fish trade, causes of this impact and proposed coping strategies. Over 50% of both fishers and fish traders believed low demand for fish from traders and a decline in the price received for fish were disrupting their lives. Approximately 75% of both male and female fishers are coping by continuing to fish, highlighting that there were few alternative livelihoods available at the time of the interviews. Our results provide key insights into the vulnerability of small-scale fishing communities to impacts of the COVID-19 pandemic. Highlights: Fishing and fish trading sharply declined due to the COVID-19 pandemic. Declines in fish prices caused disruption to fishing community livelihoods. Fishers and fish traders coped with the pandemic by continuing to fish. Coping strategies of fishers and traders to the pandemic vary with gender. Fishing communities are vulnerable to impacts of the COVID-19 pandemic.